PENERAPAN AKUNTANSI MANAJEMEN LINGKUNGAN DALAM MENINGKATKAN INOVASI PRODUK PADA PT VARIA USAHA BETON KABUPATEN SIDOARJO - Meilani Nur Maulida; Slamet Riyadi (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
PT Varia Usaha Beton is one of the manufacturing companies located in Sidoarjo Regency that produces various kinds of concrete products and provides services. In the company's operational activities, it is certainly faced with challenges related to environmental pollution and negative impacts due to its economic activities. It is becoming increasingly important for companies to maintain the sustainability of their operations and produce environmentally friendly products. The purpose of this study was to determine the application of environmental management accounting in improving product innovation at PT Varia Usaha Beton Sidoarjo Regency. This research uses qualitative research with a case study approach. The data sources used are primary data and secondary data. The data collection techniques used are observation and interviews. The results showed that the company has implemented environmental management accounting in its operational activities, but there is no specific recording. However, the provision of information to the company's stakeholders has been running well so as to provide control over activities within the company, such as information regarding the need for raw materials, the quality or quality of raw materials needed in the production process so that it affects in improving product innovation at PT Varia Usaha Beton